Stress and Sleep Disorders in Polish Nursing Students During the SARS-CoV-2 Pandemic—Cross Sectional Study - Bodys-Cupak, Iwona; Czubek, Kamila; Grochowska, Aneta (Frontiers in Psychology, 2022)
Abstract Introduction: The world pandemic of the virus SARS - CoV2 which causes COVID-19 infection appeared in December 2020. Due to the restrictions which were introduced in order to minimize the spread of the virus, people more often suffer from stress, depression, anxiety and sleep disorder. The study aim: The aim of this study was evaluation of the stress level and sleep disorder among nursing students during the pandemic SARS – CoV2. Material and study method: It was cross-sectional study conducted among 397 Polish nursing students, from two universities in southern Poland, on march 2020. The research tools: original questionnaire, Perceived Stress Scale (PSS10) and Athenian Insomnia Scale were used. Results: Respondent felt high level of stress which occurred to 68,8% interviewees if there was a danger of getting COVID-19. Those people more often protected their families from the virus. Study participants felt stress when a family member was on quarantine or worked in hospital intended for patients suffer from COVID-19. Respondents experienced stress level in 84% when a family member suffered from COVID-19. Sleep disorder was determined mainly by the fear of infection and contact with someone who might be infected with the virus. Students who felt high level of stress more often suffered from sleep disorder (70,2%), than people who felt low or average stress level (30,4%). Conclusion: Respondents felt high level of stress during the SARS-CoV2 pandemic. The high level of stress and sleep disorder appeal to students, whose family member was on quarantine, got COVID-19 or worked in the hospital intended for patients with COVID-19 infection.